(untitled) (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
This study explores the significance of experiential learning in project management education by utilising virtual tours and engaging with industry professionals. In collaboration with an external organisation, we developed a virtual tour video that showcases real world project management practices. The video provides a comprehensive view of a major project, featuring insights from more than 40 professionals. Inside the classroom, we combined this virtual tour with direct interactions with project professionals from the organisation. Students gained firsthand perspectives on how to apply theoretical concepts in practice. Feedback indicated that the virtual tour and engagement with professionals provided valuable real-world context, effectively bridging theory, and application. Students appreciated the interactive and well-structured experience. To enhance its impact further, we suggest diversifying perspectives, extending its duration, and striking a balance between theory and practical content.